Crafting Pathways to Sustainable Development: Strategic Approaches of Energy Production in OIC Nations, Pitting Renewables Against Non-Renewables - Kaki, Mohammed Ahmad (International Journal of Energy Economics and Policy, 2025)
The study examines the impact of sustainable energy production on the sustainable development of Organization of Islamic Cooperation (OIC) countries from 1990 to 2020. Focusing on integrating sustainability concepts into economic and Islamic law realms, the paper investigates directional relationships among key variables, analyzing their effects on sustainable energy consumption, renewable energy, and overall sustainable development. Robust associations are identified between energy consumption (non-renewable and renewable), economic growth, gross domestic product, trade openness, greenhouse gas emissions, and foreign direct investment. Employing the panel ARDL model for OIC countries and subgroups, the findings reveal a positive and significant impact of sustainable energy consumption on sustainable development indicators. Despite positive outcomes, challenges persist, particularly in economic diversity among studied countries, with high-income nations, primarily oil producers, struggling to address environmental concerns. Low-income countries face hurdles in achieving balanced progress toward sustainable development, as indicated by the analysis.